2017
DOI: 10.1038/s41598-017-15803-w
|View full text |Cite
|
Sign up to set email alerts
|

Sociospatial structure explains marked variation in brucellosis seroprevalence in an Alpine ibex population

Abstract: In a context of (re)emerging infectious diseases with wildlife reservoirs, understanding how animal ecology shapes epidemiology is a key issue, particularly in wild ungulates that share pathogens with domestic herbivores and have similar food requirements. For the first time in Europe, brucellosis (Brucella melitensis), a virulent zoonosis, persisted in an Alpine ibex (Capra ibex) population and was transmitted to cattle and humans. To better understand disease dynamics, we investigated the relationships betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
55
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(71 citation statements)
references
References 69 publications
2
55
0
Order By: Relevance
“…6 males and 8 females) translocated from the Mont Pleureur population in Switzerland 66 . Since the discovery of the outbreak in 2012, the population has been continuously monitored by Capture-Mark-Recapture (CMR) 29 . Using GPS data on marked individuals, Marchand et al 29 demonstrated that females are structured in five distinct socio-spatial units (SSU1-SSU5, Fig.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…6 males and 8 females) translocated from the Mont Pleureur population in Switzerland 66 . Since the discovery of the outbreak in 2012, the population has been continuously monitored by Capture-Mark-Recapture (CMR) 29 . Using GPS data on marked individuals, Marchand et al 29 demonstrated that females are structured in five distinct socio-spatial units (SSU1-SSU5, Fig.…”
Section: Methodsmentioning
confidence: 99%
“…In this context, it was critical to identify the drivers of pathogen persistence in this population and individual characteristics favoring its spread. Previous works showed that host-infectiousness vary significantly across age and sex and among socio-spatial units within the Bargy massif 29 . However, genetic factors of susceptibility to brucellosis in Alpine ibex have never been investigated while several associations with innate gene polymorphism have been discovered in domestic ungulates 31,32 .…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…Further details about the field methods for the Alpine ibex study can be found in Marchand et al. ().…”
Section: Methodsmentioning
confidence: 99%
“…While most studies on the genetic structures of H. contortus populations were performed on livestock (see [9,72]), revealing low levels of genetic differentiation even at large (e.g., state or country) spatial scales (reviewed by [33]), scarce knowledge is available in wild populations [15]. In such populations, the behavioral ecology of the host species (e.g., philopatry, sexual segregation, dispersal or migration) and landscape structure and connectivity influence host movements (e.g., [42,83]) and may generate marked socio-spatial structures at small intra population scales (e.g., [53,64]). However, how these host populations' structures influence the gene flow of their parasites is still an open question for numerous populations of wild ruminants [15].…”
Section: Introductionmentioning
confidence: 99%